Dental Caries Risk and Quality of Life of Middle Age and Older Adults during COVID-19 Pandemic in Indonesia - Zahreni Hamzah; Ari Tri Wanodyo Handayani; Amandia Dewi Permana Shita; Zahara Meilawaty; Nadia Kartikasari; Shakila Nur Aini (Association of Support to Oral Health Research (APESB), 2024)
Objective: To evaluate the correlation between caries risk and OHRQoL in middle age and the older population during the COVID-19 pandemic in Indonesia. Material and Methods: The subjects ranged in age from >45. The participants were asked to complete the Caries Management by Risk Assessment (CAMBRA) and the Oral Health Impact Profile-14  (OHIP-14) questionnaires. The data were analyzed using Mann-Whitey Test, Kruskal-Wallis Test, and Spearman Test with a significance level of p<0.05. Results: Two hundred sixteen people participated in this study. The average CAMBRA score for middle-aged and older people was 5.31 ± 1.111 and 5.27 ± 1.094, respectively. The mean scores for the OHIP-14 were 34.90 ± 6.164 for older adults and 35.79 ± 5.908 for middle-aged people. The correlation between caries risk and OHRQoL showed r=-0.400; p=0.00 for the middle age group and r=-0.143; p=0.170 for the older adults. Conclusion: During the COVID-19 pandemic in Indonesia, there was no association between caries risk and OHRQoL in the older adult population and a low correlation between caries risk and OHRQoL in the middle-aged group.